2020
DOI: 10.3390/su12073031
|View full text |Cite
|
Sign up to set email alerts
|

Leading Schools towards Sustainability. Fields of Action and Management Strategies for Principals

Abstract: Education is expected to support the development of a more sustainable way of thinking, working, and living. Although there is a broad range of literature on Education for Sustainable Development (ESD), the role of principals in the implementation of sustainability and ESD in schools has rarely been taken into consideration. However, based on the results of school effectiveness research, one can assume that school principals exert a significant influence on ESD. Sustainability is a leadership issue. When a sch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Here, STEM and social science techniques are considered together with local knowledge, stories, narratives, traditional practices, wisdom, and collective intuitions into the school practices and contents, acquiring new significant importance, especially regarding urgent topics to tackle socioecological resilience [8,9]. Furthermore, according to Ferreira et al [10], education for sustainability reinforces a systemic "whole institution approach" focused on the development of the educational facility as a whole and considers not only the role of the early childhood educators or primary teachers but also school leaders, community or state leaders, or other decisionmakers at the educational management level [11].…”
Section: Stem Education For Sustainability At An Early Stagementioning
confidence: 99%
“…Here, STEM and social science techniques are considered together with local knowledge, stories, narratives, traditional practices, wisdom, and collective intuitions into the school practices and contents, acquiring new significant importance, especially regarding urgent topics to tackle socioecological resilience [8,9]. Furthermore, according to Ferreira et al [10], education for sustainability reinforces a systemic "whole institution approach" focused on the development of the educational facility as a whole and considers not only the role of the early childhood educators or primary teachers but also school leaders, community or state leaders, or other decisionmakers at the educational management level [11].…”
Section: Stem Education For Sustainability At An Early Stagementioning
confidence: 99%
“…Only recently organizational development of schools towards sustainability and the role of school leaders were taken into consideration. Grundmann [7] conducted a study on the implementation of ESD involving teachers and principals, and Müller, Lude, and Hancock [21] developed a conceptual framework for integrating ESD in schools. Following the GAP, the Whole-Institution Approach is considered as a guideline for ESD [16].…”
Section: Esd In Germanymentioning
confidence: 99%
“…For example, Hallinger and Suriyankietkaew (2018) used science mapping tools to review 953 Scopus-indexed documents explicitly concerned with sustainable leadership and identified that most of research to date consists of case studies and single company quantitative surveys. Also, Müller et al (2020) conducted a literature review to develop a conceptual framework, which offers four stages for the integration of sustainability and ESD in a school, identifying practical actions and management strategies. Dries Verhelst et al (2020) identified the characteristics of the school facilitating ESD effectiveness through a literature review coming up with eight characteristics of an ESD-effective school organisation: sustainable leadership, school resources, pluralistic communication, supportive relations, collective efficacy, adaptability, democratic decision-making and shared vision.…”
Section: Introductionmentioning
confidence: 99%